Some aspects of оesophagus morphogenesis at the early stages of prenatal ontogenesis in human being - Marchuk O.F. (Морфологія, 2008)
The peculiarities of esophagus morphogenesis and topography formation in embryos and prefetuses of human being by the complex of morphological methods hаve been studied. Topographical differences in germ of esophagus and respiratory tube was set. In embryos of 4.5-5.0 mm PCL the process of diaphragm formation was observed, which was complete in prefetuses of 18.0-19.0 mm PCL. In embryos of 9.0-9.5 mm PCL the enlarge of circular layer of esophagus muscular membrane was observed; in embryos of 18.0-19.0 mm PCL the longitudinal layer was enlarged. In further development a circular layer thickness was in prevalence due to the thickness of longitudinal layer along all length of esophagus. As a result of condensing interorganic layers of mesenchyma more close correlative intercommunications between esophagus, trachea, thoracic aorta, vagus nerves and serous membranes was set. At the end of prefetuses period the process of recanalisation of esophagus was completed.